Design and development of mobile application for parking reservation system / Ray Adderley JM. Gining ...[et al.] - JM Gining, Ray Adderley; Fauzi, S.S.M; Jamaluddin, Muhammad Nabil Fikri; Marizalee, Muhammad Akram; Razak, Tajul Rosli; Sharip, Anis Afiqah (UiTM Cawangan Perlis, 2019)
Every emerging country face the issue of public parking congestion in the urban area. Ignoring the issue would breed a series of problems; from traffic disruption to violating the laws related to traffic. In Malaysia, the City Council has made an effort to mitigate the problem by using a coupon - which largely handled manually by the user by purchasing and paying the coupon through a machine. However, the procedure of using a coupon is considered inefficient due to challenges such as; extensive time, coupon exploitation and material waste. Therefore, to mitigate the problem surfaced in the current procedure, a mobile application is developed to handle the parking reservation process. The reservation process included the function to view the parking's availability thus presented the user the advantage of reserving parking earlier in the case of parking usage are at the peak. This paper highlighted the requirement identification and design and development phases.